(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2019)
This article investigates the stylistic features of Yusuf Xos Hojib’s Qutadg‘u bilig, a foundational monument of 11th-century Turkic literature that merges political philosophy, ethical instruction, and poetic artistry. While previous research has extensively analyzed its linguistic and historical dimensions, there remains a notable gap regarding how contemporary readers and scholars perceive its layered stylistic strategies. To address this, the study adopts a qualitative, survey-based approach, gathering insights from linguistic experts, philology scholars, and advanced students familiar with the text. Through systematic coding and thematic analysis of survey responses, the research identifies three dominant stylistic categories: didactic symbolism, phonetic ornamentation, and lexical-cultural hybridity. The findings reveal that these stylistic devices not only enhance the aesthetic and rhetorical dimensions of the text but also serve critical pedagogical and ideological functions, transmitting cultural values and ethical norms across generations. The results suggest that integrating such classical stylistic models into modern language education could strengthen cultural literacy and foster a deeper appreciation of Turkic literary heritage. Furthermore, the study highlights the need for expanded interdisciplinary research — including computational stylistic analysis and cross-cultural comparisons — to deepen our theoretical understanding and broaden the practical applications of medieval Turkic literary studies. Ultimately, this research contributes to filling the knowledge gap on stylistic reception and reinforces the enduring significance of Qutadg‘u bilig within the broader context of world literature.